Intuitionistic fuzzy ideals of BCK-algebras - Young Bae Jun; Kyung Ho Kim (International Journal of Mathematics and Mathematical Sciences)
We consider the intuitionistic fuzzification of the concept of subalgebras and ideals in BCK-algebras, and investigate some of their properties. We introduce the notion of equivalence relations on the family of all intuitionistic fuzzy ideals of a BCK-algebra and investigate some related properties.